Analysis of the Effectiveness of Grimloc Store Bandung's Physical Releases Marketing Strategy - Fazri, Revi Muhamad; Yunani, Akhmad (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to assess the effectiveness of Grimloc Store Bandung's marketing strategy through quantitative descriptive research. The analysis reveals that the implementation of a new strategy in 2022 had no positive impact on incremental sales and cost efficiency at Grimloc Store. Both pre- and post-sale strategies exhibited no significant difference in Return on Marketing Investment (ROMI), indicating an overall lack of ROMI impact. The study observes no substantial increase in incremental sales after the 2022 strategy implementation compared to the previous year. ROMI, a key metric, gauges the efficiency of marketing spend in generating incremental revenue. Calculated by dividing the difference between incremental sales and incremental cost by the incremental cost itself, then multiplying by 100, similar ROMI values suggest that every Rupiah invested in marketing did not significantly contribute to revenue growth. The t-test results, with a recorded t-count value of 0.055 below the t-table value of 2.074 (t-count < t-table), reject the null hypothesis, indicating that the 2022 marketing strategy did not notably enhance sales performance and cost efficiency. Therefore, Grimloc Store's physical release strategy is deemed ineffective.